The Physical Activity in the Management of Heart Failure with Reduced Ejection Fraction A Review of Current Evidence and Recommendations - Natalia Smyl; Mateusz Teofilak; Olga Śpiołek; Jan Siwiec; Aleksandra Słowikowska; Julia Szatkowska; Marcelina Paula Sztyler-Krąkowska; Agnieszka Alicja Wąsowicz; Franciszek Kędziora; Dariusz Paweł Fabian (Quality in Sport, 2025)
Heart failure with reduced ejection fraction (HFrEF) remains a chronic cardiovascular condition characterized by increased morbidity and mortality. Advancements in pharmacological therapy is abundant, but there is mounting recognition for non-pharmacological approaches such as structured physical activity for improving life quality and functional capability. Current recommendations suggest the addition of physical exercises as a complementary treatment for patients with HFrEF, and the strength of recommendations is backed by a considerable amount of evidence. This review aims to synthesize current scientific evidence regarding the role of physical activity in the management of patients with HFrEF, with a focus on its impact on clinical outcomes, including prognosis, functional capacity, and quality of life. Additionally, it seeks to provide recommendations on the types, intensity, and modalities of exercise best suited to this population. A comprehensive search of the literature was conducted using databases such as PubMed, UpToDate, ScienceDirect, and Google Scholar. The review included studies evaluating exercise interventions in HFrEF populations, focusing on clinical outcomes, safety considerations, and recommendations from leading cardiology societies. The analysis confirms that dynamic aerobic training, resistance training, and inspiratory muscle training for breathing and pulmonary rehabilitation constitute the most effective exercise strategies for HFrEF patients and their impact on exercise ability and functional quality of life is substantial. While meta-analyses do not consistently demonstrate a reduction in all-cause and cardiovascular mortality, cardiac rehabilitation based on physical exercise remains fundamental in the treatment of HFrEF. Individualized exercise prescriptions based on the FITT-VP model (Frequency, Intensity, Time, Type, Volume, and Progression) are encouraged to improve patient results.